(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The Accountancy, Business, and Management strand is part of the K-12 Academic Track. It focuses on financial management, business management, corporate operations, and everything that needs to be recorded. However, this study focuses on evaluating the factors that influenced the Grade 11 and Grade 12 ABM students in terms of choosing Accountancy, Business, and Management as their preferred track and how they perceived their track as a contribution to their future course. This study is conducted at Bestlink College of the Philippines, Bulacan Inc. The study revealed that in terms of factors that influence students in choosing a strand, personal interest got the highest composite mean of 3.43, interpreted as strongly Agreeable. Moreover, for the research question of how respondents perceive their track as a contribution to their future course, it got a 3.53 Mean, and the interpretation of that is Strongly Agree. The findings let the researchers know that students choose ABM because of their personal interests, and students perceived their track as a contribution to their future course because it is connected to the course that they want to take in college. Additionally, ABM strand subjects would give them primary knowledge that would be helpful to their future course. Furthermore, ABM Students strongly agreed that the wrong choice of track might affect their future course. The ABM strand is part of the K-12 Academic Track. It focuses on financial management, business management, corporate operations, and everything that needs to be recorded. In Bestlink College of the Philippines, Bulacan Inc., most Grade 11 and Grade 12 ABM students pursued this strand because of their personal interest, and they can see that Accountancy, Business, and Management have a contribution to the course that they will take in college. The researchers recommend students know what they truly want and seek information on how their chosen track would impact them as they go beyond Senior High School.